Isolation and Characterization Endophytic Fungal Isolate from Peronema canescens Jack Leaf and Coptosapelta tomentosa Val. K. Heyne Root - Arsyik Ibrahim; M. Arifuddin; Wisnu Cahyo P; Wahyu Widayat; Mahfuzun Bone (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2019)
Has been done Isolation, Characterization and Secondary Metabolite Endophytic Fungal Isolate from Peronema canescens Jack Leave and Coptosapelta tomentosa Valeton K. Heyne Root. The aim of this research is to know the number of fungal isolates, chromatogram profile and secondary metabolite group of endophytic fungal isolates from P. canencens leaves and C. tomentosa root. Characterization of endophytic fungal isolates was done macroscopically and microscopically. Identification of secondary metabolites endophytic fungal isolates were performed by chemical reaction test and TLC (Thin Layer Chromatography) method with specific spray reagents. The data of this study were obtained based on the number of endophytic fungal that can be isolated, observing macroscopic and microscopic morphological profiles, chromatogram profile and secondary metabolites of each endophytic fungal isolated. The results showed that endophytic fungal that can be isolated from P. canencens leaves four isolates, and two isolates from C. tomentosa root. Morphological profile macroscopic endophytic fungal of the six isolates showed a greenish-colored colony, white gray, clear black. Microscopic profile of each fungal isolate having spores, sprangiosphora, sporangium, conidia, hyphae and stolon. The identified secondary metabolites are: alkaloids, terpenoids, and flavonoids, and polyphenols.